Investigation into the bond strength of bitumen-fibre mastic. (30th November 2018) - Mohammed, Monketh; Parry, Tony; Thom, Nick; Grenfell, James
Highlights: Adding fibre led to an increased pull-off tensile strength of the mastic. A general reduction in the pull-off tensile strength of the 1.2 f/b ratio at 2% fibre. Adding fibre changing the failure mode from cohesive to hybrid. The contact angle results for each drained binder varied within a narrow range. There is a good agreement between work of the cohesion and pull-off tensile strength. Abstract: The loss of bond strength in road pavement surfacing due to high traffic loads or moisture is a recurring problem, creating distresses such as ravelling, fatigue and rutting. It is, therefore, important to find a way to prevent or at least delay the loss of bond strength in asphalt mixtures. Such an improvement would lead to longer service life and a more comfortable drive for road users. This study describes how the pneumatic adhesion tensile testing instrument (PATTI) was used to examine the mechanism by which fibres influence the pull-off tensile strength of asphalt mastic. This study assesses the potential for chemical modification of the binder due to the presence of fibres, by means of work of cohesion and work of adhesion calculations, based on surface energy parameters and a binder drainage test. The study also evaluates the influence of different filler-bitumen ratios and fibre percentages on pull-off tensile strength. The test results indicate that the fibres enhance the pull-off tensile strength of the mastic, in addition to changing the failure mode from cohesive to hybrid, implying an improvement in the cohesive strength of the mastic.